The effectiveness of using a preparation containing amino acids in the cultivation of strawberries under thermal stress conditions - Zydlik, Piotr; Zydlik, Zofia; Wieczorek, Robert (Polish Journal of Agronomy, 2021)
The research was carried out in 2018 at the experimental station of the University of Life Sciences in Poznań. The plants of the strawberry variety Albion were exposed to sub-zero temperatures in the white bud phase and in full bloom. The possibility of mitigating the results of strawberries subjected to thermal stress was investigated using the Terra-Sorb complex biostimulator with a high content of amino acids. The intensity of flowering, the number, weight and area of strawberry leaves, the number of fruits on a bush and their quality parameters such as fruit weight, extract content and firmness were analysed. It was established that the impact of the sub-zero temperature on strawberry shrubs, regardless of the development phase of the plant, the number of inflorescences and healthy flowers was reduced significantly, the number of fruits, their average weight and firmness decreased. The use of the biostimulator on plants exposed to temperatures from -2 to -3 °C contributed to increasing the number of healthy strawberry flowers by several percentage points, the number of fruits per plant and increased their average weight significantly. The extract content in strawberries remained unchanged.